Influence of local tetracycline on the microbiota of alveolar osteitis in rats - Bosco, Joseane Maria Dias [UNESP]; Oliveira, Sérgio Ricardo de [UNESP]; Bosco, Álvaro Francisco [UNESP]; Schweitzer, Christiane Marie; Jardim Júnior, Elerson Gaetti [UNESP] (FapUNIFESP (SciELO), 2008)
The aim of the present study was to evaluate the effects of local tetracycline on the occurrence of alveolar osteitis in rats, and on the microbiota associated to this infection. Forty Wistar rats were randomly assigned to 4 groups (n=10): I - the rats had the maxillary right incisor extracted and the alveolar wound did not receive any treatment; II - adrenaline and Ringer-PRAS were introduced into the alveolar wound; III - the alveolar wound was irrigated with sterile saline; and IV - the alveolar wound was irrigated with an aqueous solution of tetracycline. Microbial samples from the alveolar wounds were collected 2 days after surgery and inoculated on blood agar (with and without 8 μg/mL of tetracycline) and other selective media, and were incubated in either aerobiosis or anaerobiosis at 37°C, for 2 to 14 days. It was verified that tetracycline reduced the occurrence of alveolar osteitis in the rats and caused significant changes in the microbiota of the surgical sites, decreasing the number of anaerobes and increasing the participation of tetracycline-resistant and multi-resistant microorganisms.
Keywords: Alveolar osteitis; Antimicrobials; Dry alveolus; Microorganisms; Tetracycline; adrenalin; antiinfective agent; isotonic solution; Ringer's solution; tetracycline; unclassified drug; vasoconstrictor agent; Actinomyces; animal; antibiotic resistance; bacterial count; Bacteroides; comparative study; drug effect; Enterobacteriaceae; Enterococcus; Eubacterium; Fusobacterium; incisor; lavage; male; microbiology; multidrug resistance; Peptostreptococcus; randomization; rat; suppuration; tooth extraction; tooth pain; tooth socket; Veillonella; Wistar rat; Animals; Anti-Bacterial Agents; Colony Count, Microbial; Drug Resistance, Multiple, Bacterial; Dry Socket; Epinephrine; Incisor; Irrigation; Isotonic Solutions; Male; Random Allocation; Rats; Rats, Wistar; Suppuration; Tetracycline Resistance; Tooth Extraction; Tooth Socket; Vasoconstrictor Agents